2009
DOI: 10.3332/ecancer.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-Myc oncoprotein in oral squamous cell carcinoma in the south Indian population

Abstract: Oral neoplasm constitutes a predominant class of cancer that is encountered in South India. This is in large part due to the elevated risk of oncogenesis as a result of the habit of chewing of quids containing betel leaves, areca nut and smokeless tobacco. An array of molecular events are induced during the transformation of the buccal epithelium, among them the over-expression of oncogene products plays a key role. The c-Myc protein, a regulator of a number of key cellular signalling pathways, plays a pivotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Consistent with the above finding overexpression of p53 in the nuclei of epithelial cells of PHT induced GO tissues have been observed (Saito, 1999). Both the overexpression of mitogenic factors and p53 has been observed in oral dysplastic and precancerous lesions, and has been frequently associated with the development of a wide range of carcinomas including OSCCs (Haque, 1998;Wakulich, 2002;Abbas, 2007;Angiero, 2008;Bishen, 2008;Pai, 2009;). Incidentally, cyclosporine-an immunosuppressant and nifedepine-a calcium channel blocker induce GO and OSCCs have been reported to arise from these tissues as well (Varga, 1991;Pahor, 1996).…”
Section: Introductionsupporting
confidence: 69%
“…Consistent with the above finding overexpression of p53 in the nuclei of epithelial cells of PHT induced GO tissues have been observed (Saito, 1999). Both the overexpression of mitogenic factors and p53 has been observed in oral dysplastic and precancerous lesions, and has been frequently associated with the development of a wide range of carcinomas including OSCCs (Haque, 1998;Wakulich, 2002;Abbas, 2007;Angiero, 2008;Bishen, 2008;Pai, 2009;). Incidentally, cyclosporine-an immunosuppressant and nifedepine-a calcium channel blocker induce GO and OSCCs have been reported to arise from these tissues as well (Varga, 1991;Pahor, 1996).…”
Section: Introductionsupporting
confidence: 69%
“…c-Myc is a known oncogene, as well as target gene, in various types of cancers, including lung ( 7 – 10 ) and breast cancer ( 10 – 12 ), and hepatocellular carcinoma ( 13 , 14 ). Previous studies showed that the c-Myc protein was overexpressed in 80% of the OSCC ( 15 ), Genome-wide profiling of OSCC has also shown that, among other genes, gain of c-Myc gene occurred at a high frequency ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, with the help of IHC, attempt has been made to explore the changes in expression of two important molecules related to stemness of the oral stem cells and in this respect the two markers that have been tried are K19, (19), (20), (21), (22) and c-Myc. (23), (24), (25) Though, the expression of K19 and c-Myc on oral dysplasia and oral cancer have been done earlier but, so far, no study has been carried out to look into the expression of these two proteins in the same tissue to characterize the basal stem cells and transient amplifying cells.…”
Section: Discussionmentioning
confidence: 99%